Investigation of some production factors on yield and quality of dry beans - Nemeskéri, E. (International Journal of Horticultural Science, 2002)
The correlation between plant density and yield average shows that the volume of yield increases in varieties of large and medium-size seeds up to a plant density of 285-400 thousand/ha, after which it declines. On the basis of the results, yield averages at plant densities of 285-334 thousand plant/ha are 0.17 t/ha higher than those achieved at low density (200 thousand plant/ha). High levels of potassium fertilizer did not enhance the yield of dry beans. With adequate-water supply the high level of potassium decreased the number of pods and seeds per plant compared with a basic level of fertilizer, which could ensure 2.5 t/ha yield.